The application of mesoporous silica nanoparticles as a drug delivery vehicle in oral disease treatment - Fang, Lixin; Zhou, Huoxiang; Cheng, Long; Wang, Yiyi; Liu, Fei; Wang, Suping (Frontiers in Cellular and Infection Microbiology, 2023)
Mesoporous silica nanoparticles (MSNs) hold promise as safer and more effective medication delivery vehicles for treating oral disorders. As the drug’s delivery system, MSNs adapt to effectively combine with a variety of medications to get over systemic toxicity and low solubility issues. MSNs, which operate as a common nanoplatform for the co-delivery of several compounds, increase therapy effectiveness and show promise in the fight against antibiotic resistance. MSNs offer a noninvasive and biocompatible platform for delivery that produces long-acting release by responding to minute stimuli in the cellular environmen. MSN-based drug delivery systems for the treatment of periodontitis, cancer, dentin hypersensitivity, and dental cavities have recently been developed as a result of recent unparalleled advancements. The applications of MSNs to be embellished by oral therapeutic agents in stomatology are discussed in this paper.